Factors related to aggressive behaviors among older adults in nursing homes of Korea: A cross-sectional survey study. (December 2018) - Choi, Hyoungshim; Jung, Young-Il; Kim, Hongsoo
Abstract: Background: Aggressive behavior is one of the most challenging behavioral psychological symptoms for older adults and their caregivers in nursing homes. Objectives: The purpose of this study was to examine and identify contributing factors of aggressive behaviors among older adults in nursing homes in South Korea. Design: This is a secondary analysis of a national survey on health and functional status among older nursing home residents. Settings: Participants were recruited from 91 nursing homes. Participants: A total of 1447 older adults were included for final analysis and they were randomly selected from a nationally representative sample of people 65 years and older at the sampled nursing homes. Methods: Presence of aggressive behaviors was identified when participants showed at least one of the five symptoms in the Korean interRAI Long-Term Care Facility Assessment Tool such as physical abuse, verbal abuse, socially inappropriate or destructive behaviors, and resistance to care. Theory-based contributing factors were selected and examined. Multivariate logistic regression analyses were performed. Results: About 19% of older nursing homes residents had aggressive behaviors, and several health and social factors including social engagement are associated with aggressive behaviors. Conclusions: Aggressive behavior is prevalent in older nursing home residents with and without dementia in South Korea and individual and institutional level interventions are necessary.